The Impact of Depression on the Functional Outcome of the Elderly Stroke Victim from a Gender Perspective: A Systematic Review - Franco-Urbano, María Salud; Rodríguez-Martínez, María del Carmen; García-Pérez, Patricia (IOAP-MPDI, 2022)
(1) Background: The aim of this systematic review focused on analyzing the impact of depression on the functional outcome of the elderly stroke victim and how this disorder affects both the female and the male population. (2) Methods: We conducted a systematic review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The review was registered in PROSPERO (ID 346284). The systematic search for clinical trials was performed in the databases Pubmed, Otseeker, Scopus, Web of Science, Psycinfo, Medline Complete, ScienceDirect, SciELO, and Dialnet. Articles were selected according to the inclusion and exclusion criteria, including those dealing with post-stroke depression in adults whose psychological status had changed. Studies that only assessed the psychological state of caregivers were excluded. (3) Results: In total, 609 articles were identified, of which 11 randomized controlled trials were finally included in the review. The results indicate that post-stroke depression influences the recovery of functionality and quality of life. In addition, the need to detect the mood of the adult population after the stroke and to provide individualized treatment according to the characteristics of the person is highlighted. (4) Conclusions: This systematic review shows how early detection of post-stroke depressive symptoms can improve the degree of disability and quality of life of the person, especially in women.
Keywords: Depresión; Stroke; Depression; Treatment outcome; Quality of life